(untitled) (Research, Society and Development, 2024)
To analyze the profile of security incidents reported in a hospital institution in Mato Grosso. This is a quantitative, descriptive and retrospective research, based on Patient Safety incident notification forms from a hospital institution. Between October 2021 and December 2022, 2,157 notifications were made from the researched hospital, of which 486 were related to patient safety. It was observed that the sector with the highest prevalence of patient safety incident episodes were the Support Sectors for inpatient units. According to the characterization of the types of incidents, the Adverse Event appears in a greater number of notifications, then the Incident without damage. In relation to the Patient Safety Goals, there was a prevalence of Goal 3 - “Safe use of high-alert medications. From the results obtained in this study, it was evident that the majority of notifications made in the hospital institution researched do not correspond to patient safety incidents, requiring the application of knowledge in Patient Safety and expansion of the Patient Safety Culture . It is suggested that new research be developed on this topic, in order to identify the relationship between educational activities and error notifications in the hospital context. Thus, incident notification is considered to be a fundamental quality tool, as it allows improving healthcare assistance.